Asymmetric Electrode for Suppressing Cell Swelling in Commercial Lithium Ion Batteries. Issue 10 (10th August 2015) - Zhang, Ningxin; Tang, Huaqiong; Zhang, Lisi; Trifonova, Atanaska
Abstract : Swelling is an inevitable phenomenon in intercalation type anodes such as graphite due to the expansion of its crystalline lattice during lithiation. The stress accumulation due to anode swelling upon cycling would lead to the deterioration of discharging capacities as well as cell thickening in commercial lithium ion batteries. To suppress cell thickening, a novel asymmetric electrode is designed, so that the electrode thicknesses on the opposite sides of the current collector differ from each other. A series of thickness ratios (1.00, 1.05, 1.10 and 1.15) was prepared, and the thicker side of the anode film was wound inwardly. Upon cycle testing, the group with a thickness ratio of 1.05 showed the highest consistency in capacity retention ratio and the least swelling. This is ascribed to the asymmetric electrode configuration, which directs compressive force inward, thereby tightening the jelly-roll.